Risk and time preferences of farmers in India and Indonesia - Arieska Wening Sawosri; Oliver Mußhoff (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2020)
This cross-country study compares risk and time preferences of farmers from two lower-middle income countries, India and Indonesia. Current literature mainly focuses on a single country context; however, this study involves more than one country. Hence, we could investigate whether the individual preferences of farmers from two countries with similar income level are the same. The preferences are key for the policymakers to make informed policy decisions regarding investments and acceptance of development programs. Our study involved 1,528 farmers. The risk and time preferences were elicited using incentivised experiments and simultaneously estimated following the joint-estimation-method by Andersen et al. (2008). Results show that the farmers in India show a higher level of risk aversion and lower discount rates, even though very high discount rates were encountered in both countries. As a result, policymakers should consider implementing policies to deal with high discount rates causing poverty and lack of investment.
urn:nbn:de:gbv:7-webdoc-4004-7
Keywords: 330; Cross-country dataset; lower-middle income countries; risk preferences; smallholder farmers; time preferences